Preparation and stress-strain behavior of in-situ epoxidized natural rubber/SiO2 hybrid through a sol-gel method - S. M. Li; T. W. Xu; Z. X. Jia; B. C. Zhong; Y. F. Luo; D. M. Jia; Z. Peng (eXPRESS Polymer Letters)
In this paper, epoxidized natural rubber was reinforced by silica generated in-situ though the sol-gel method using tetraethoxysilane(TEOS) as precursor. The results showed that the ring opening reaction of epoxy group appeared in the in-situ reaction progress, where the hydrogen bond between Si–OH and C–OH was mainly formed to enhance the stress-strain behavior of ESH simultaneously. During the hot pressing progress, the compound was crosslinked via the chemical reaction of Si–OH and C–OH. The chemical bond between Si–OH and C–OH reinforced rubber-filler interaction, resulting further improved the stress-strain behavior. Besides, comparing with precipitated SiO2 filled ENR, the dispersion of SiO2 in ENR matrix was distinctly more uniform though the sol-gel method, along with the enhancement of mechanical properties. Herein, our findings open up a new way to prepare an environmentally friendly rubber composite with excellent dispersion and strong rubber-filler interaction without curing agent effectively.